PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA LAZADA (STUDI KASUS PADA MAHASISWA STIESIA SURABAYA) - Silaban, Tio Krista; Rochdianingrum, Widhi Ariestanti (LPPM STIE YKPN Yogyakarta, 2024)
Increasingly tight competition in the marketplace forces Lazada to continue to innovate to attract consumers to make purchases at Lazada. This research aims to determine the influence of Service Quality, Trust and Promotion on purchasing decisions at Lazada. The population used in this research were students from the Surabaya College of Economics class of 2019. The sampling technique used accidental sampling on students from the Surabaya College of Economics class of 2019 who met the specified criteria, namely 89 people. The analytical tool used in this research is SPSS 20. The research results show that service quality has a positive and significant influence on purchasing decisions at Lazada, namely by providing quality service it will increase consumer purchasing decisions towards Lazada. Trust has a positive and significant effect on purchasing decisions because by increasing consumer trust, they will not hesitate to use Lazada as their purchasing decision. Promotion has a positive and significant effect on purchasing decisions because by carrying out promotions that are right on target, many consumers will be interested and increase purchasing decisions. Simultaneously, service quality, trust and promotion have a positive and significant effect.